2010
DOI: 10.2528/pierb10070107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Design of an Uhf Rfid Metal Tag Using Magnetic Composite Material as Substrate

Abstract: Abstract-Using magnetic composite material as the substrate for RFID metal tag has several advantages over conventional metal tags, such as flexibility and miniaturized size. In this paper, the radiation intensity contributed by a half-wave dipole is derived based on the result of an ideal Hertzian dipole, which leads to a simple relation for thin substrate. Later on, the material constants of two materials are measured and the one capable of generating greater radiation intensity is used in the course of ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…However, since most tags use a dielectric material [8][9][10][11] or high impedance surface substrate [12] to make an interval between the tag antenna and the attached surface and slit metallic plate with the appearance of a window [13], the price and the size prevent from applying them widely.…”
Section: Brief Introduction Of the Proposed Systemmentioning
confidence: 99%
“…However, since most tags use a dielectric material [8][9][10][11] or high impedance surface substrate [12] to make an interval between the tag antenna and the attached surface and slit metallic plate with the appearance of a window [13], the price and the size prevent from applying them widely.…”
Section: Brief Introduction Of the Proposed Systemmentioning
confidence: 99%
“…When 0 < h < λ/4 is fulfilled, the gain will increase with h. And the reading distance r will exceed 2 meters at some distance near λ/4. Magnetic substrate can be effectively applied to decline the distance h [8,12]. In order to obtain a small, thin and efficient antenna, µ r and ε r of the magnetic substrate cannot be too large because large electromagnetic parameters can greatly affect the aperture efficiency.…”
Section: Analysis Of Antenna Parametersmentioning
confidence: 99%
“…The main solutions include inserting a dielectric layer between the antenna pattern and the metal ground or even using special antenna design principles to avoid metal interference [2][3][4][5][6], but their uses are limited by the considerable prices. Recently, a series of novel RFID metal tags are proposed, for instance, tag equipped with Artificial Magnetic Conductor reported by Abu et al [7] and tag equipped with magnetic composite material reported by Kuo et al [8]. The use of magnetic substrate opens up opportunities for solving metal interference problem.…”
Section: Introductionmentioning
confidence: 99%
“…In the scientific literature, there are some prominent studies dealing with the design of tags nonvulnerable to the above phenomena [24][25][26][27][28][29][30].…”
Section: Electromagnetic Noise Absorption and Reflectionmentioning
confidence: 99%